The Implementation of Restorative Justice in Juvenile Narcotics Cases: A Comparative Study of Islamic Law and Indonesian Positive Law in Tanjung Jabung Barat Regency - Dasep Nurdin; Ahmad Syukri; Yuliatin Yuliatin; Abdul Halim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
For criminal justice systems, the growing number of young people involved in drug-related crimes is a serious problem, especially when it comes to striking a balance between law enforcement and child protection and rehabilitation. By contrasting viewpoints from Islamic law and Indonesian positive law, this study investigates the use of restorative justice in the processing of adolescent drug cases in Tanjung Jabung Barat Regency, Jambi. The study used a qualitative socio-legal methodology that integrates normative legal analysis with empirical field data gathered via observations, interviews, and document analysis involving law enforcement personnel, rehabilitation facilities, families, and community people. The results show that diversionary measures required by Law No. 11 of 2012 regulating the Juvenile Criminal Justice System are the main means by which restorative justice is applied in juvenile drug cases. In order to guarantee that children are not subjected to punitive detention but rather have options for recovery and social reintegration, these systems prioritize mediation, rehabilitation, and community involvement. From the standpoint of Islamic law, restorative justice is consistent with fundamental tenets like tawbah (repentance), islah (reconciliation), and the protection of human welfare, all of which place an emphasis on moral reform and the preservation of children's dignity. These ideas support the adoption of restorative measures in the resolution of adolescent drug offenses in Tanjung Jabung Barat, a sociocultural setting where Malay-Islamic beliefs have a significant impact on community life. The report does, however, also point out a number of difficulties, such as the lack of rehabilitation facilities, the societal stigma associated with juvenile offenders, and the inconsistent use of diversion by law enforcement. The study comes to the conclusion that a framework for handling juvenile drug cases that prioritizes the rehabilitation and future well-being of children is both culturally sensitive and legally sound when restorative justice ideas are integrated with Islamic legal values and Indonesian statutory law.